Hypertension and Anaesthesia - Des Lines (South African Family Practice)
The difficulty that anaesthetists face is that they often, when seeing a patient pre-operatively, do not have the benefit of seeing the patient’s “normal average” blood pressure taken at different times over a period of weeks. The decision to cancel surgery based on the blood pressure found at the pre-operative visit must, therefore, take into account the urgency of the surgery, as well as the presence of end organ damage from chronic hypertension. A detailed history and examination should be performed looking for evidence of coronary artery disease, cerebrovascular disease and renal dysfunction.